2019
DOI: 10.1042/bsr20180896
|View full text |Cite|
|
Sign up to set email alerts
|

Targetting an LncRNA P5848-ENO1 axis inhibits tumor growth in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has a high recurrence rate and poor clinical outcome after currently used therapies, including radiofrequency ablation. To explore the possible mechanisms for the relapse of HCC, in the present study we focussed on long non-coding RNA (LncRNA), which has been reported to be involved in tumorigenesis. We identified an LncRNA P5848, whose expression level was up-regulated in tumor samples from HCC patients after radiofrequency ablation. As such, we speculated that LncRNA P5848 may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Therefore, further studies should be performed to identify other glycolytic enzymes in cancer progression. Recently, the glycolytic enzyme ENO1 has attracted the attention of oncologists because it is dys-regulated in various cancer types, including gastric cancer, HCC, glioma and pancreatic cancer [14,30–32]. However, it remains unknown whether ENO1 serves as a tumor suppressor, oncogene or neither in BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further studies should be performed to identify other glycolytic enzymes in cancer progression. Recently, the glycolytic enzyme ENO1 has attracted the attention of oncologists because it is dys-regulated in various cancer types, including gastric cancer, HCC, glioma and pancreatic cancer [14,30–32]. However, it remains unknown whether ENO1 serves as a tumor suppressor, oncogene or neither in BC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ENO1 is a potential biomarker for hepatocellular carcinoma (HCC) [13]. It serves as a target for LncRNA P5848 and promotes tumor growth and survival in HCC [14]. Targeting ENO1 suppresses the proliferation and growth of gastric cancer cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…22 It was also noticed that ENO1 promoted cancer progression in hepatocellular carcinoma, breast cancer, and gastric cancer. 10,[23][24][25] Generally, most studies support the idea that ENO1 expression is elevated and promotes the Warburg effect and cancer proliferation and invasion; ENO1 overexpression and modifications have diagnostic and prognostic value. 26 However, it may play distinctive roles in different cancer types.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, upregulated a-enolase expression has been shown to regulate cell proliferation in various solid tumours in vitro [11,13,[57][58][59][60][61] , and to increase tumour growth in a HCT116 colorectal cancer xenograft model in vivo [11] [ Table 2]. Conversely, silencing of a-enolase in glioma, pancreatic, lung, endometrial, colorectal and breast cancer cells was found to induce cell cycle arrest and senescence, and also to reduce tumour volume in CFPAC-1 pancreatic, MDA-MB-231 breast and U-87MG glioma xenograft models in vivo [6,11,12,62,63] .…”
Section: Increased Alpha-enolase Expression Enhances Cell Proliferatimentioning
confidence: 99%
“…Overexpression of a-enolase has been shown to increase the migration and invasion of hepatocellular carcinoma, colorectal and gastric cancer cells in vitro [11,58,60,61,67] and to enhance colorectal cancer metastasis in vivo [11] , demonstrating that it is an important driver of metastasis in multiple cancer types [ Table 3]. Conversely, knockdown or pharmacological inhibition of a-enolase decreased the migration and invasion of glioma, colorectal, pancreatic and endometrial carcinoma in vitro [6,12,63,68,69] , and decreased tumourigenesis and metastasis of endometrial carcinoma in vivo [12] .…”
Section: Role In Invasion and Migrationmentioning
confidence: 99%